Recombination and dynamics of transposable elements in natural populations. A drosophilist’s view - Kozeretska, I.A. (Вiopolymers and Cell, 2011)
The concept of the tight link between crossing over and the dynamics of transposable elements is presented. The behavior of transposable elementsinfluences the processes of homologous recombination, both at the moment of activation and as a result the changes in a genome caused by active transposition of the autonomous nucleotide sequences. Keywords: crossing over, transposable elements, drosophila. Викладено уявлення про те, що процеси кросинговеру та динаміки мобільних генетичних елементів перебувають у тісному взаємозв’язку. Поведінка мобільних елементів геному впливає на процеси гомологічної рекомбінації як безпосередньо в момент активації, так і внаслідок змін, що відбуваються в геномах у результаті активного переміщення автономних нуклеотидних послідовностей. Ключові слова: рекомбінація, мобільні генетичні елементи, дрозофіла Изложено представление о том, что процессы кроссинговера и динамики мобильных генетических элементов находятся в тесной взаимосвязи. Поведение мобильных элементов генома влияет на процессы гомологичной рекомбинации как непосредственно в момент активации, так и вследствие изменений, происходящих в геномах в результате активного перемещения автономных нуклеотидных последовательностей. Ключевые слова: рекомбинация, мобильные генетические элементы, дрозофила.